Identifikasi Faktor-Faktor Internal dan Eksternal dalam Analisis Strategi yang Memungkinkan Bagi Penyelenggaraan Haji Ramah Lingkungan - Nasution, Azizah Hanim (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2023)
This article aims at providing an overview of how the Pilgrimage can be developed into an Environmentally -Friendly Hajj Pilgrimage (HRL) and has the potential to participate massively in reducing the impact of climate change. Several literature studies are presented as an attempt to prove the importance of the theological relationship between God, humans and the environment. The Ministry of Religion of North Sumatra Province is expected to be able to initiate the HRL movement and inovates the implementation of the Hajj to be more meaningful to Islam, Iman, and Ihsan. SWOT analysis is carried out by determining internal and external factors which are summarized from several literature reviews. To confirm the causal relationship between factors, another analysis was carried out using the Causal Loop Diagram approach. From the results of the analysis it was found that the most possible strategy for the Regional Office of the Ministry of Religion of North Sumatra Province to initiate HRL. Keywords: HRL, SWOT, CLD